Assessing the Availability and Allocation of Production Capacity in a Fabrication Facility Through Simulation Modeling: A Case Study - Marvel, J. H; Schaub, M. A; Weckman, G. R (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
For a tier two automobile supplier’s fabrication facility, the manufacturing process required producing two classes of products, those produced on a repetitive and those produced on a periodic basis. Static capacity analysis determined if sufficient gross capacity existed in the production system in order to meet customer demand but was unable to determine if the capacity was available at the desired times to preserve an acceptable service level. A simulation model was developed to confirm the sequencing and scheduling of both classes of products. The model also incorporated the logistical constraints of customer supplied materials used in the production process. The simulation output was able to evaluate the system performance metrics regarding material availability, transportation efficiencies, product backorders, and interruptions to the production process. The model provided a planning tool that assessed the quarterly production plan; identified customer service issues and evaluated the impact of continuous improvement efforts.